Motivation for Educational Attainment in Grade 9 Predicts High School Completion. Issue 2 (29th January 2019) - West, Stephen G.; Hughes, Jan N.; Kim, Han Joe; Bauer, Shelby S.
Abstract: The Motivation for Educational Attainment (MEA) questionnaire, developed to assess facets related to early adolescents' motivation to complete high school, has a bifactor structure with a large general factor and three smaller orthogonal specific factors (teacher expectations, peer aspirations, value of education). This prospective validity study investigated the utility of each factor in predicting high school dropout or completion of a general education development (GED) certificate versus completion of a high school degree. Participants were 474 (55.1% male) ethnically diverse students who were originally recruited into a larger longitudinal study in Grade 1 on the basis of academic risk. Fourteen years later, 373 had obtained a high school diploma, 15 had obtained a GED, and 86 had dropped out of high school. During their first year of Grade 9, participants were administered the MEA. Using multinomial logistic regression with high school graduation as the reference outcome and controlling for Grade 9 letter grades, reading and math test scores, gender, and ethnic/racial group status, scores on the latent general factor and the latent peer aspirations factor predicted high school dropout versus high school graduation status. Neither the general factor nor any of the three specific factors predicted GED completion versus high school graduation. Ethnicity, but not gender, moderated the associations between scores on the general factor and high school graduation versus dropout.